Utilisation of growth monitoring service by mothers of infants in Mettu town, Southwest Ethiopia - Yohanis Tufa; Abeza Mitiku; Shuayib Shemsu; Kebebe Bidira (BMJ Publishing Group, 2022)
Background Growth monitoring (GM) is a preventive activity that serves as the core function in an integrated child health and nutrition programme. In most developing nations, including Ethiopia, however, the use of GM service is insufficient. Hence, the purpose of this study was to evaluate the use of GM services and associated characteristics among mothers of infants in Mettu town, Southwest Ethiopia.Objective To assess the utilisation of GM service by mothers of infants in Mettu town, Southwest Ethiopia, 2021.Method A community-based cross-sectional study was conducted among 354 randomly selected mothers with children aged 0-23 months old from 25 June to 27 July 2021 in Mettu town. EpiData V.4.6.0 was used to enter data, which were then exported to SPSS V.25 for analysis. Simple binary and multivariable logistic regression analyses were performed to identify factors associated with GM service utilisation.Results A total of 354 study participants were included in the study, yielding a response rate of 95.2%. The proportion of GM service utilisation was 25.2% (95% CI: 20.24% to 29.33%). In multivariable regression analysis, age of index child 0-11 months (AOR (adjusted OR)=1.58; 95% CI: 1.052 to 3.713), early postnatal care (PNC) (AOR=1.72; 95% CI: 1.657 to 6.467), middle tertile wealth status (AOR=0.108; 95% CI: 0.047 to 0.319) and lower tertile wealth status (AOR=0.073; 95% CI: 0.013 to 0.874), utilisation of family health cards (AOR=2.09; 95% CI: 1.384 to 5.343) and taking ≤30 min to reach the nearest health facility (AOR=2.23; 95% CI: 2.061 to 7.350) were significantly associated with GM service utilisation.Conclusion and recommendation In this study, only one-fourth of mothers with children aged 0-23 months old were using GM services. GM service utilisation was found to be significantly associated with child age, early PNC visit, wealth status, utilisation of family health cards and time taking ≤30 min to reach the nearest health facility. Hence, appropriate strategies that promote and encourage GM service utilisation should be designed.